Let's play tic-tac-toe: Confucius Institutes versus American Cultural Centres. Issue 2 (3rd April 2022) - Lien, Donald; Tang, Peilan
Abstract: China and the United States (US) have established respective cultural institutions in each other, namely the Confucius Institute and the American Cultural Centre. While they differ in the establishment background and management model, in their counterpart countries' view, both Confucius Institutes and American Cultural Centres serve the function of public diplomacy as a 'quasi-diplomatic agency', attracting extensive political attention. When comparing the history of their developments in the US and China, a similar trend of 'rise-to-fall' and 'positivity-to-negativity' can be observed. The stagnation of American Cultural Centres in China and the crisis of Confucius Institutes in the US both originate from the same source — political pressure. The development paths of both institutions are closely related to the development and transformation of Sino–US political relations. In this process, China's attitude is relatively moderate in an attempt to maintain the continuous development of a friendly bilateral relation, while the US is anxious about China's rising status as its economic and strategic competitor, thereby adjusting its China policy and imposing rigid political controls over Confucius Institutes. Affected by the Sino–US trade dispute and the COVID-19 pandemic, Sino–US relations deteriorate further; accordingly, the future outlook of Confucius Institutes in the US is worrying. However, with abundant uncertainties, the future of the Confucius Institute remains to be further studied.